LANGUAGE STYLE USED IN ENGLISH ADVERTISEMENTS ON FACEBOOK: STYLISTIC ANALYSIS - Silvia Kumala Wati; Sufiyandi Sufiyandi; Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2019)
This research is about study of language style used in English advertisements on Facebook. The aims of this research are: (1) to explain the kinds of language style that are mostly used in English advertisements in Facebook. (2) to explain the way of language style convey the messages of English advertisements in Facebook to the customer. This research uses qualitative research as method. The technique of collecting the data, the writer uses download, documentation and note taking technique. The using of stylistics in this research has some kinds that used on advertisements and also used to get the meaning of advertisements it selves. So that, the kinds of style of stylistics can explain the result as well. The result of this research is alliteration is mostly used in advertisement because it appears five times. Advertiser uses language style as message to attract customer to embellish advertisement itself. Key Words:   language style, advertisement, stylistics, Facebook.